PENGEMBANGAN STRATEGI PEMASARAN PRODUK OLAHAN SUSU “KOMIKU” PADA MERRY FOODIES LOMBOK TIMUR - Ni Nyoman Suli Asmara Yanti (Institut Agama Hindu Negeri Gde Pudja Mataram, 2022)
Milk is a food that is rich in benefits and nutrients. There are many benefits obtained from the content of milk, making milk produced by many producers. One of the home industries that produces dairy products is Merry Foodies, which is located in Selong, East Lombok Regency, West Nusa Tenggara Province. The business idea of ​​making Komiku dairy products originated from the phenomenon of public interest, especially the Indonesian people who are interested in things that are related to the South Korean state, including processed food products that are often shown on South Korean television shows. In this study, we will discuss how to develop a marketing strategy for